Pretreatment fluid suitable for repairing shaft integrity casing cement sheath

By using emulsified pretreatment liquid in the gaps of the casing cement ring to improve the surface wettability, the problem of poor gap repair effect in the prior art is solved, and the corrosion resistance of the casing is improved by forming a protective film.

CN119823736AActive Publication Date: 2025-04-15CHINA NATIONAL OFFSHORE OIL (CHINA) CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411932291.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The prior art has poor results in repairing casing cement ring gaps, especially in micro cracks.

Method used

A pretreatment liquid, including bisphenol A type epoxy resin, catalyst A, catalyst B, solvent, alkoxylation reagent and pH adjuster, is made by emulsification, and is used to circulate the broken point before pumping the repair material to improve the wettability of the surface at the broken point.

Benefits of technology

By improving surface wetting, improving the repair effect at the gaps, and improving the corrosion resistance of the inner surface of the casing by forming a protective film, avoiding corrosion damage to the fluids that enter the well.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a pre-treatment fluid suitable for repairing a cement sheath of an integrity casing of a shaft. The pretreatment liquid is prepared from bisphenol A epoxy resin, a catalyst A, a catalyst B, a solvent, an alkoxylation reagent and a pH regulator through an emulsification effect, the catalyst A is one or more of tetrabutylammonium chloride, triethanolamine, sodium hydroxide, magnesium hydroxide and boron trifluoride diethyl etherate; the catalyst B is one or more of sodium acetate, ammonium chloride, boron trifluoride and stannic chloride. According to the method, the broken point can be circularly treated before the repair material is pumped, the wettability of the surface of the broken point is improved, and the improvement of the repair effect is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil and gas well plugging and oil and gas production, and relates to a pre-treatment fluid suitable for repairing a casing cement ring of a wellbore integrity. Background Art

[0002] In the oil industry, many factors (such as large-scale acid fracturing, geology, plastic creep and corrosion of salt rock, etc.) can cause different degrees of deformation of the casing cement ring, especially in the underground formations that are prone to collapse, serious plastic creep and poor cementing quality, which not only seriously affects the safety and benefits of oil and gas fields, but also causes huge economic losses to major oil fields. At present, the commonly used technologies for the repair of casing cement ring include casing patching technology, casing replacement technology, small casing secondary cementing technology and ash squeezing plugging technology. Among them, ash squeezing plugging technology is the most commonly used technology. By squeezing the plugging agent into the broken section of the casing and plugging the broken point after solidification, it has good pressure bearing capacity and large diameter, and can be applied to the repair of various damage conditions. The other three technologies are not suitable for the repair of micro cracks in the casing cement ring due to high construction cost, difficulty in implementation, high equipment requirements and other problems.

[0003] The ash squeezing and plugging technology repairs the leak by squeezing materials into the leaking point. If the repair material cannot be tightly bonded to the surface of the broken point after solidification, the repair effect will be seriously affected. Summary of the invention

[0004] In view of the problem that the existing repair technology has poor repair effect on the casing / cement ring gap, the purpose of the present invention is to provide a pre-treatment fluid suitable for wellbore integrity casing cement ring repair, which can indirectly promote the repair effect of the casing / cement ring gap.

[0005] The present invention can perform circulation treatment on the broken point before pumping the repair material, thereby improving the wettability of the surface of the broken point and promoting the improvement of the repair effect.

[0006] The present invention provides a pre-treatment fluid suitable for wellbore integrity casing cement ring repair, which comprises bisphenol A type epoxy resin, catalyst A, catalyst B, solvent, alkoxylation agent and pH regulator prepared by emulsification;

[0007] The catalyst A is one or more of tetrabutylammonium chloride, triethanolamine, sodium hydroxide, magnesium hydroxide, and boron trifluoride ether;

[0008] The catalyst B is one or more of sodium acetate, ammonium chloride, boron trifluoride and tin tetrachloride.

[0009] In the above-mentioned pretreatment liquid, the weight ratio of the bisphenol A epoxy resin, catalyst A, solvent, catalyst B, and alkoxylating agent is 1:0.001-0.005:1-3:0.0008-0.009:0.5-1.5.

[0010] In the pretreatment liquid of the present invention, the weight ratio of the bisphenol A epoxy resin, the catalyst A, the solvent, the catalyst B, and the alkoxylating agent may be 1:0.002:1.4:0.001:1.2 or 1:0.0016:1.6:0.0008:1.

[0011] In the above-mentioned pretreatment solution, the pH adjusting agent adjusts the pH of the pretreatment solution to 6-7.

[0012] In the above-mentioned pre-treatment liquid, the solvent is one or more of stearic acid, isostearic acid, lauric acid and palmitic acid.

[0013] In the above-mentioned pretreatment liquid, the alkoxylation agent is one or more of ethylene oxide, propylene oxide and butylene oxide.

[0014] In the above-mentioned pretreatment liquid, the pH adjuster is one or more of hydrochloric acid, sulfuric acid, propionic acid, and dodecylbenzenesulfonic acid.

[0015] In the above-mentioned pre-treatment liquid, the viscosity of the pre-treatment liquid is 0-50 cP, and the density is 1-1.05 g / cm 3 .

[0016] The present invention also provides a method for preparing the above-mentioned pretreatment liquid, comprising the following steps: 1) stirring and mixing the bisphenol A type epoxy resin and the catalyst A, adding the solvent after heating to react, testing the epoxy value of the system, and stopping the reaction when the epoxy value no longer changes;

[0017] 2) adding the catalyst B to the reaction system of step 1), and continuously adding the alkoxylation agent under vacuum conditions after heating, and continuing the reaction until the system pressure is negative and the pressure does not change, and then stopping the reaction;

[0018] 3) Cooling the reaction system in step 2) to 50-70° C. (specifically 65° C.), adding the pH adjuster to adjust the pH of the system, thereby obtaining a pretreatment solution.

[0019] In the above method, in step 1), the temperature is raised to 140-160°C, specifically 150°C.

[0020] In the above method, in step 2), the temperature is 170-190°C, specifically 180°C.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The pre-treatment fluid of the present invention can not only clean the surface of the casing cement ring gap, change the surface wettability, and improve the repair effect of the surface at the gap, but also the pre-treatment fluid can be adsorbed on the inner surface of the wellbore casing to form a protective film, thereby improving the corrosion resistance of the inner surface of the casing and avoiding corrosion damage caused by the fluid in subsequent well operations. DETAILED DESCRIPTION

[0023] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0024] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0025] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0026] The invention provides a pre-treatment fluid suitable for wellbore integrity casing cement ring repair, which comprises bisphenol A type epoxy resin, catalyst A, catalyst B, solvent, alkoxylation agent and pH regulator and is prepared by emulsification.

[0027] Furthermore, in the pretreatment liquid, the weight ratio of the bisphenol A epoxy resin, the catalyst A, the solvent, the catalyst B, and the alkoxylation agent is 1:0.001-0.005:1-3:0.0008-0.009:0.5-1.5.

[0028] The present invention also provides a method for preparing the above-mentioned pretreatment liquid, comprising the following steps: 1) stirring and mixing the bisphenol A type epoxy resin and the catalyst A, heating to 140-160° C., adding the solvent to react, testing the epoxy value of the system, and stopping the reaction when the epoxy value no longer changes;

[0029] 2) adding the catalyst B to the reaction system of step 1), heating to 170-190° C. under vacuum conditions, continuously adding the alkoxylation agent, and continuing the reaction until the system pressure is negative and the pressure no longer changes, then stopping the reaction;

[0030] 3) Cooling the reaction system in step 2) to 50-70° C., adding the pH adjuster to adjust the pH of the system, thereby obtaining a pretreatment solution.

[0031] Example 1

[0032] In a reactor, 500 g of bisphenol A epoxy resin and 1 g of triethanolamine were stirred and mixed uniformly, the temperature was raised to 150° C., 700 g of palmitic acid was added to the reactor for reaction, the epoxy value of the system was tested, and the epoxy value no longer changed. Then 0.5 g of sodium acetate was added to the reactor and vacuum was applied; the temperature was raised to 180° C., 600 g of ethylene oxide was continuously added, and the reaction was continued until the pressure in the reactor was negative and the pressure no longer changed; the heating was turned off, the reactor was circulated and cooled, the system temperature was reduced to 65° C., sulfuric acid was added to the reactor to adjust the pH of the system to 7, and pretreatment liquid A1 was obtained.

[0033] The surface tension of the pre-treatment liquid was tested according to GB / T 5549-2010 "Determination of surface tension of surfactants by pulling up liquid film method", and the test result was 35.14mN / m. The viscosity of the pre-treatment liquid at 25℃ was tested according to GB / T 11145-2014 "Determination of low temperature viscosity of lubricants by Brokfeldt viscometer method", and the test result was 45cP.

[0034] Example 2

[0035] In a reactor, 500 g of bisphenol A epoxy resin, 0.5 g of tetrabutylammonium chloride and 0.5 g of triethanolamine were stirred and mixed evenly, and the temperature was raised to 150° C., 800 g of lauric acid was added to the reactor for reaction, and the epoxy value of the system was tested. The epoxy value no longer changed, and then 0.4 g of ammonium chloride and 0.3 g of tin tetrachloride were added to the reactor, and vacuum was applied; the temperature was raised to 180° C., and 500 g of ethylene oxide was continuously added, and the reaction was continued until the pressure in the reactor was negative and the pressure no longer changed; the heating was turned off, the reactor was circulated and cooled, the system temperature was reduced to 65° C., and propionic acid was added to the reactor to adjust the pH of the system to 7, and pretreatment liquid A2 was obtained.

[0036] The surface tension of the pre-treatment liquid was tested according to GB / T 5549-2010 "Determination of surface tension of surfactants by pulling up liquid film method", and the test result was 30.56mN / m. The viscosity of the pre-treatment liquid at 25℃ was tested according to GB / T 11145-2014 "Determination of low temperature viscosity of lubricants by Brokfeldt viscometer method", and the test result was 42cP.

[0037] Example 3

[0038] In a reactor, 500 g of bisphenol A epoxy resin and 0.5 g of boron trifluoride ether were stirred and mixed uniformly, the temperature was raised to 150° C., 600 g of isostearic acid was added to the reactor for reaction, the epoxy value of the system was tested, and the epoxy value no longer changed. Then 0.4 g of boron trifluoride was added to the reactor and vacuum was applied; the temperature was raised to 180° C., 400 g of propylene oxide was continuously added, and the reaction was continued until the pressure in the reactor was negative and the pressure no longer changed; the heating was turned off, the reactor was circulated and cooled, the system temperature was reduced to 65° C., and hydrochloric acid was added to the reactor to adjust the pH of the system to 7, thereby obtaining a pretreatment liquid A3.

[0039] The surface tension of the pre-treatment liquid was tested according to GB / T 5549-2010 "Determination of surface tension of surfactants by pulling up liquid film method", and the test result was 32.28mN / m. The viscosity of the pre-treatment liquid at 25℃ was tested according to GB / T 11145-2014 "Determination of low temperature viscosity of lubricants by Brokfeldt viscometer method", and the test result was 44cP.

[0040] Comparative Example 1

[0041] In a reactor, 500 g of bisphenol A epoxy resin was stirred and mixed uniformly, the temperature was raised to 150° C., 600 g of palmitic acid was added to the reactor for reaction, the epoxy value of the system was tested, and the epoxy value no longer changed. Then 0.4 g of sodium acetate was added to the reactor and vacuum was applied; the temperature was raised to 180° C., 400 g of propylene oxide was continuously added, and the reaction was continued until the pressure in the reactor was negative and the pressure no longer changed; the heating was turned off, the reactor was circulated and cooled, the system temperature was reduced to 65° C., and hydrochloric acid was added to the reactor to adjust the pH of the system to 7, thereby obtaining a pretreatment liquid A4.

[0042] The surface tension of the pre-treatment liquid was tested according to GB / T 5549-2010 "Determination of surface tension of surfactants by pulling up liquid film method", and the test result was 20.58mN / m. The viscosity of the pre-treatment liquid at 25℃ was tested according to GB / T 11145-2014 "Determination of low temperature viscosity of lubricants by Brokfeldt viscometer method", and the test result was 58cP.

[0043] Comparative Example 2

[0044] In a reactor, 500 g of bisphenol A epoxy resin and 0.5 g of boron trifluoride ether were stirred and mixed uniformly, the temperature was raised to 150 ° C, 600 g of isostearic acid was added to the reactor for reaction, the epoxy value of the system was tested, and the epoxy value did not change, the temperature was continued to be raised to 180 ° C, 400 g of propylene oxide was continuously added, and the reaction was continued until the pressure in the reactor was negative and the pressure did not change; the heating was turned off, the reactor was circulated and cooled, the system temperature was reduced to 65 ° C, and hydrochloric acid was added to the reactor to adjust the pH of the system to 7, and the pretreatment liquid A5 was obtained.

[0045] The surface tension of the pre-treatment liquid was tested according to GB / T 5549-2010 "Determination of surface tension of surfactants by pulling up liquid film method", and the test result was 22.46mN / m. The viscosity of the pre-treatment liquid at 25℃ was tested according to GB / T 11145-2014 "Determination of low temperature viscosity of lubricants by Brokfeldt viscometer method", and the test result was 52cP.

[0046] (1) Wetting performance test

[0047] Surface wettability of cement block: Cement slurry was prepared according to the formula (the formula was: water + 300g G-grade cement), poured into a mold after preparation, placed in a 60°C water bath and taken out after it was completely cured, and then placed in the pre-treatment liquids A1 to A5 prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and in distilled water and soaked for 24 hours and then dried. Subsequently, the contact angles of distilled water with the untreated cement block and the cement block treated with the pre-treatment liquid were measured using a fully automatic contact angle meter. The specific test results are shown in Table 1.

[0048] Table 1 Contact angle with cement block

[0049] Serial number Type of solution for soaking cement blocks Contact angle θ / ° 1 Pretreatment liquid A1 122.5 2 Pretreatment liquid A2 138.2 3 Pretreatment fluid A3 167.0 4 Pretreatment fluid A4 76.9 5 Pretreatment fluid A5 57.6 6 Distilled water 29.1 7 Not soaked 26.8

[0050] Simulating the wettability of the casing surface: The commonly used J-55 casing material was processed into a test piece (length 30 mm, width 30 mm, height 2 mm). After the test piece was polished and rusted, it was cleaned with ethanol and immersed in the pretreatment liquids A1 to A5 prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and in distilled water for 24 hours and then dried. Subsequently, the contact angles of distilled water with the untreated test piece and the test piece treated with the pretreatment liquid were measured using a DSA100 contact angle meter. The specific test results are shown in Table 2.

[0051] Table 2 Contact angle with specimen

[0052] Serial number Immersion test piece solution type Contact angle θ / ° 1 Pretreatment liquid A1 115.8 2 Pretreatment liquid A2 128.1 3 Pretreatment fluid A3 161.5 4 Pretreatment fluid A4 83.0 5 Pretreatment fluid A5 53.7 6 Distilled water 22.8 7 Not soaked 20.2

[0053] It can be seen from Tables 1 and 2 that the contact angles of the cement blocks and test pieces after being soaked in pre-treatment liquids A1-A6 change, and the wettability changes. The surfaces of the cement blocks and test pieces treated with the pre-treatment liquids A1-A3 prepared in Examples 1 to 3 of the present invention change from hydrophilic to lipophilic, and the cement blocks and test pieces treated with pre-treatment liquid A3 have the best lipophilic effect. The contact angles of the cement blocks and test pieces treated with the pre-treatment liquids A4 and A5 prepared in Comparative Examples 1 to 2 change, but they still show hydrophilicity. This is mainly because no corresponding catalyst was added to the pre-treatment liquids A4 and A5 prepared in Comparative Examples 1 to 2 during the emulsification process, resulting in poor wetting reversal ability of the synthesized treatment liquids.

[0054] (2) Anti-corrosion ability

[0055] The commonly used J-55 casing material was processed into a test piece (with a length of 30 mm, a width of 30 mm, and a height of 2 mm). The test piece was polished and rusted, then cleaned with ethanol, placed in a 60°C oven for drying for 24 hours and weighed. Then the weighed test piece was placed in the pre-treatment liquid A1~A5 prepared in Examples 1~3 and Comparative Examples 1~2 and soaked in distilled water for 24 hours and then taken out. After being corroded in a 10% hydrochloric acid environment for 30 days, the sample was taken out to remove the loose corrosion products on the surface, and then rinsed with distilled water. It was also placed in a 60°C oven for drying for 24 hours and then weighed. The anti-corrosion efficiency was calculated according to the petroleum and natural gas standard SY / T5273-2000, thereby characterizing the anti-corrosion ability of the pre-treatment liquid A1~A5 prepared in Examples 1~3 and Comparative Examples 1~2. The specific test results are shown in Table 3.

[0056] Table 3 Anti-corrosion ability

[0057] Serial number Immersion test piece solution type Anti-corrosion efficiency / % 1 Pretreatment liquid A1 95.83 2 Pretreatment liquid A2 96.92 3 Pretreatment fluid A3 98.71 4 Pretreatment fluid A4 66.16 5 Pretreatment fluid A5 59.52 6 Distilled water 42.38 7 Not soaked 38.95

[0058] It can be seen from Table 3 that the corrosion resistance of the specimens treated with the pre-treatment liquids A1-A5 prepared in Examples 1 to 3 and Comparative Examples 1 to 2 is significantly improved, among which the specimens treated with the pre-treatment liquid A3 have the strongest corrosion resistance, indicating that the protective film formed on the surface of the specimen by the pre-treatment liquid A3 of the present invention has a strong and dense structure, which can prevent the fluid from contacting the specimen and avoid the specimen from being corroded and damaged.

[0059] In summary, the pretreatment fluid of the present invention can indirectly improve the repair effect of the gap between the casing and the cement ring. It can not only clean the surface of the gap between the casing and the cement ring, change the surface wettability, and improve the repair effect of the surface at the gap, but also form a protective film by being adsorbed on the inner surface of the wellbore casing, thereby improving the corrosion resistance of the inner surface of the casing and avoiding corrosion damage caused by the fluid in subsequent well operations.

[0060] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A pre-treatment fluid suitable for wellbore integrity casing cement ring repair, characterized in that: The invention comprises bisphenol A type epoxy resin, catalyst A, catalyst B, solvent, alkoxylation agent and pH regulator and is prepared by emulsification; The catalyst A is one or more of tetrabutylammonium chloride, triethanolamine, sodium hydroxide, magnesium hydroxide, and boron trifluoride ether; The catalyst B is one or more of sodium acetate, ammonium chloride, boron trifluoride and tin tetrachloride.

2. The pretreatment liquid according to claim 1, characterized in that: In the pretreatment liquid, the weight ratio of the bisphenol A epoxy resin, catalyst A, solvent, catalyst B, and alkoxylation agent is 1:0.001-0.005:1-3:0.0008-0.009:0.5-1.

5.

3. The pretreatment liquid according to claim 1 or 2, characterized in that: The pH adjuster adjusts the pH of the pretreatment solution to 6-7.

4. The pretreatment liquid according to any one of claims 1 to 3, characterized in that: The solvent is one or more of stearic acid, isostearic acid, lauric acid and palmitic acid.

5. The pre-treatment liquid according to any one of claims 1 to 4, characterized in that: The alkoxylating agent is one or more of ethylene oxide, propylene oxide and butylene oxide.

6. The pre-treatment liquid according to any one of claims 1 to 5, characterized in that: The pH regulator is one or more of hydrochloric acid, sulfuric acid, propionic acid, and dodecylbenzenesulfonic acid.

7. The pre-treatment liquid according to any one of claims 1 to 6, characterized in that: The viscosity of the pretreatment liquid is 0-50 cP, and the density is 1-1.05 g / cm 3 .

8. The method for preparing the pretreatment liquid according to any one of claims 1 to 7, comprising the following steps: 1) stirring and mixing the bisphenol A epoxy resin and the catalyst A, adding the solvent after heating to react, testing the epoxy value of the system, and stopping the reaction when the epoxy value does not change; 2) adding the catalyst B to the reaction system of step 1), and continuously adding the alkoxylation agent under vacuum conditions after heating, and continuing the reaction until the system pressure is negative and the pressure does not change, and then stopping the reaction; 3) Cooling the reaction system in step 2) to 50-70° C., adding the pH adjuster to adjust the pH of the system to 6-7, thereby obtaining a pretreatment solution.

9. The method according to claim 8, characterized in that In step 1), the temperature is raised to 140-160°C.

10. The method according to claim 8 or 9, characterized in that: In step 2), 170-190°C.

Citation Information

Patent Citations

  • Oil-gas well cementation cement sheath self-repair solution and preparation and application thereof

    CN103952129A

  • Bi-oleophilic-group modified bisphenol-A epoxy resin surfactant and preparation method and application thereof

    CN110105542A

  • Modified epoxy resin emulsion for well cementing slurry and preparation method of modified epoxy resin emulsion

    CN118048130A

  • Blowing agent incorporated resin systems for consolidating subterranean oil and gas bearing formations

    US20230183556A1